2022
DOI: 10.3389/fonc.2022.875761
|View full text |Cite
|
Sign up to set email alerts
|

The Machine Learning Model for Distinguishing Pathological Subtypes of Non-Small Cell Lung Cancer

Abstract: PurposeMachine learning models were developed and validated to identify lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC) using clinical factors, laboratory metrics, and 2-deoxy-2[18F]fluoro-D-glucose ([18F]F-FDG) positron emission tomography (PET)/computed tomography (CT) radiomic features.MethodsOne hundred and twenty non-small cell lung cancer (NSCLC) patients (62 LUAD and 58 LUSC) were analyzed retrospectively and randomized into a training group (n = 85) and validation group (n = 35). A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The gold standard of histological classification is pathological evaluation. At present, many techniques can be used for tissue diagnosis and the preferred choice is image-guided needle core biopsy ( 38 ). Unfortunately, as an invasive examination, the operational risks of biopsy are inevitable, including a series of complications such as infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The gold standard of histological classification is pathological evaluation. At present, many techniques can be used for tissue diagnosis and the preferred choice is image-guided needle core biopsy ( 38 ). Unfortunately, as an invasive examination, the operational risks of biopsy are inevitable, including a series of complications such as infection.…”
Section: Resultsmentioning
confidence: 99%
“…Zhao et al. use the Boruta algorithm to determine an optimal subset of 13 features, including two clinical features(sex and smoking history), two laboratory indicators(CEA and SCCA), and nine PEF/CT radiomic features ( 38 ). The clinical features they included were the same as those of Ren et al ( 44 ), but there were differences in laboratory indicators.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the results of the LR model, the results of the RF model showed that clinical biochemical indicators are generally better predictors of risk than general demographic characteristics and previous pregnancy history. This is probably because the variable lter of the RF model is not sensitive to indicators that appear less frequently in the dataset [55] . It is di cult for logistic regression model to apply to collinear variables and it has poor prediction ability for high-dimensional, multi-sample, non-linear data.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 Associating image features with tumor gene–protein features or tumor phenotypes can develop models for cancer diagnosis, patient prognosis, or relative tumor heterogeneity, especially for patients who are unable to perform biopsy or whose biopsy fails. 23 In the long run, radiomics will not replace the role of radiologists. Instead, it will be a powerful tool for radiologists.…”
Section: Discussionmentioning
confidence: 99%